The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/carcin/bgt291
|View full text |Cite
|
Sign up to set email alerts
|

Delphinidin is a novel inhibitor of lymphangiogenesis but promotes mammary tumor growth and metastasis formation in syngeneic experimental rats

Abstract: We have recently demonstrated that the anthocyanidin delphinidin (DEL), one of the most abundant dietary flavonoids, inhibits activation of ErbB and vascular endothelial growth factor receptor family members. These receptors play crucial roles in the context of tumor progression and the outgrowth of blood and lymphatic vessels. Here, we have developed an improved chemical synthesis for DEL in order to study the effects of the aglycon and its degradation product gallic acid (GA) on endothelial and tumor cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Recently, it was demonstrated that delphinidin blocks the proliferation of primary human blood and lymphatic endothelial cells as well as carcinoma cells in vitro in a dose-dependent manner. At higher concentrations, apoptosis of endothelial and tumor cells was induced [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was demonstrated that delphinidin blocks the proliferation of primary human blood and lymphatic endothelial cells as well as carcinoma cells in vitro in a dose-dependent manner. At higher concentrations, apoptosis of endothelial and tumor cells was induced [25].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in another study in vivo administration of delphinidin significantly reduced angiogenesis in the MT-450 rat syngeneic breast tumor model, although tumor growth and metastasis were promoted. The antiproliferative effect of delphinidin on cultured cells does not necessarily reflect the response of tumors to this anthocyanidin in vivo [25].…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] Most protease methods utilize combinations of different collagenases and DNase. There are several products that are commercially available including dispase, 11 liberase, [12][13][14][15][16] elastase, 17,18 and purified collagenases. 8,[19][20][21] The targets of these enzymes and reaction conditions are described in Table 1.…”
Section: Cell Isolation Methodsmentioning
confidence: 99%
“…Regarding the mechanism of anti‐cancer effects, both the inhibition of receptor tyrosine kinases like the epidermal growth factor receptor (EGFR) and the catalytic inhibition of topoisomerases might contribute to this effect . However, there is also some contradiction, as the application of DEL as a free aglycon has been found to promote tumor growth and metastasis formation in rats .…”
Section: Introductionmentioning
confidence: 99%